Asuhan Keperawatan pada Klien yang Mengalami Masalah Harga Diri Rendah pada Skizofrenia Paraniod di Ruang Kasuari RSJ Dr. Soeharto Heerdjan Jakarta - Trisongko, Didi; Prihatini, Fitria; Elwindra, Elwindra (Jurnal Persada Husada Indonesia, 2024)
Low Self-Esteem is a feeling of shame or inferiority due to shortcomings in oneself. Caused by negative judgments from self and others in the same environment. Of all schizophrenic clients, 40% had self- concept problems: low self-esteem. The purpose of the study was to conduct nursing care on low self- esteem problems with schizophrenia in the Cassowary room of Dr. Soeharto Heerdjan Mental Hospital, Jakarta. The design used a case study with the subject of 2 clients with the same nursing problem and diagnosis i.e. self-concept problem: low self-esteem with schizophrenia. Data collection using interviews, observation and physical examination. The results of the research after being carried out SP1 and SP2 both clients can achieve result criteria such as: in SP1 tidying the mattress, sweeping, mopping the floor, friendly facial expressions, good eye contact between clients and hospital nurses. The client is able to answer greetings well. In SP2 clients are also able to perform scheduled activities such as sweeping, mopping floors, making mattresses and a positive list of environments: being able to interact with fellow clients and nurses. The conclusion of the application of SP1 and SP2 is that the client is able to increase his self-esteem. The author's suggestion hopes that the next SP can be done for families with family activities present so that the problem of low self-esteem is more effective in achieving it. The result of this study is that problems can be overcome. Identify and train client skills, teach interacting with others and maintain personal hygiene. It is recommended that mental health program holders counsel clients and families on how to reduce the risk of recurrence in clients: implement strategies to implement low self- esteem in clients and families.